2014
DOI: 10.1186/1472-6947-14-49
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire survey about use of an online appointment booking system in one large tertiary public hospital outpatient service center in China

Abstract: BackgroundAs a part of nationwide healthcare reforms, the Chinese government launched web-based appointment systems (WAS) to provide a solution to problems around outpatient appointments and services. These have been in place in all Chinese public tertiary hospitals since 2009.MethodsQuestionnaires were collected from both patients and doctors in one large tertiary public hospital in Shanghai, China.Data were analyzed to measure their satisfaction and views about the WAS.ResultsThe 1000 outpatients randomly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 30 publications
3
43
0
1
Order By: Relevance
“…With the prevalence of EAS in the health care sector, studies on patient acceptance and usage of EAS services have been conducted [ 31 , 32 ]. Cao et al [31] conducted a qualitative study to examine patient usage of a web-based appointment system implemented in a Chinese public tertiary hospital [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the prevalence of EAS in the health care sector, studies on patient acceptance and usage of EAS services have been conducted [ 31 , 32 ]. Cao et al [31] conducted a qualitative study to examine patient usage of a web-based appointment system implemented in a Chinese public tertiary hospital [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the study of Zhang et al, about patients' experience of web based appointment system using online appointment websites in a hospital in China, the most tolerable waiting time for visiting the doctor was 30 minutes. (10) This time was about 10-20 minutes in our study. Additionally, in Zhang's research, satisfaction with the waiting time (P=0.01) was signi cantly different among native, nonnative and passenger patients.…”
Section: Discussionmentioning
confidence: 61%
“…Also in one study by Finkelstein et al, entitled "Priorities of appointment reminder systems and patient", the use of this facility was reported in 2.66% of all systems studied in Colombia (33), although in a study from Norway, 45.45% of hospital appointment systems were able to recall the appointment (34), which is not consistent with the current study. The reviewed studies revealed that post-appointment recall probability significantly contributed to the system flexibility, time management (15), reduction in the number of missed appointments (14,15,24,25,33,34) and costs (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/) which permits copy and redistribute the material just in noncommercial usages, provided the original work is properly cited time and any place, allowing the user to see the physicians' appointments (9), selection of the desired option, editing the recorded information, more favorable relationship between physician and patient, improvement of the efficiency and effectiveness of care (5), cost reduction (11)(12)(13)(14), reduction of the number and volume of employees (7), saving patient information for use in subsequent appointments (11), and reduction of the number of missed appointments (9,11,(13)(14)(15)(16)(17)(18). However, despite the importance of this system, a few studies have been done on its evaluation and existing researches in this field have investigated topics, such as designing a web-based appointment system (19), patient satisfaction of online appointment booking systems (4,20), development of information technology acceptance model for an online appointment booking system in hospitals (21)(22)(23), implementation and use of the online appointment booking system in clinics (15,20), and improving the management of appointments (24,25). There are limited studies in Iran on the need for smart systems to prepare an optimized program for patients and investigating the appointment-making system of private physicians' offices (5,22).…”
Section: Introductionmentioning
confidence: 99%